Topological spaces with the Freese–Nation property - Bąk, Judyta; Kucharski, Andrzej (Annales Mathematicae Silesianae, 2019)
We give a proposal of generalization of the Freese–Nation property for topological spaces. We introduce a few properties related to Freese–Nation property: FNS, FN, FNS*, FNI. This article presents some relationship between these concepts. We show that spaces with the FNS property satisfy ccc and any product of such spaces also satisfies ccc. We show that all metrizable spaces have the FN property.